"Home Charms": unpacking an Irish immigrant woman's home through speculative design. Issue 4 (2nd October 2019) - Gillett, Molly-Claire
ABSTRACT: Maeve Brennan's 1953 short story "The Bride, " describes the isolation and complicated homesickness of a young Irish woman living as a domestic servant in New York. Taking Brennan's story as a starting point, this paper uses a designed and made object – a set of digitally modeled and 3D printed Home Charms –as research-creation based methodology to investigate the spatial, material, and performative implications of settlement in a new domestic space, especially for women who lived, worked, and were conceptually identified with the home, its architecture and material culture.